Polanyi neu entdecken: Freiheit, Demokratie und Sozialismus - Novy, Andreas (Rediscover Polanyi: Freedom, democracy and socialism., 2018)
Political Science
Keywords: BRIE; Michael; Karl Polanyi's Vision of a Socialist Transformation (Book); NONFICTION; Polanyi neu entdecken: Das hellblaue Bandchen zu einem moglichen Dialog von Nancy Fraser und Karl Polanyi (Book); THOMASBERGER; Claus; book review; fiction; nonfiction

Karl Polanyi - The Life and Works of an Epochal Thinker - Thurnher, Armin; Aulenbacher, Brigitte; Novy, Andreas; Marterbauer, Markus; Polanyi Levitt, Kari (2020)
On 8 May 2018, the International Karl Polanyi Society was founded in Vienna. This marked the beginning of a new phase of engagement with a thinker who had already come to be regarded as a centennial figure in the Anglo-Saxon world. This book serves as an introduction to The Great Transformation, Polanyi’s magnum opus and one of the most important works of the 20th century. It helps us to understand the background to Karl Polanyi’s intellectual career, sketches the lives of his family members, describes the milieus of Budapest, Vienna, London and New York, which were such informative influences in his life, and sheds light on his relationship with contemporaries such as Keynes, Mises and Hayek. Renowned Polanyi researchers, including, most notably his daughter Kari Polanyi Levitt, elucidate Polanyian concepts such as ‘fictitious commodities’ and apply his analysis to an era when everything seems to be subjected to the mechanics of the market.
Sociology
Keywords: Great Transformation; The (Book); fictitious commodities